Single-Walled Carbon Nanotubes Mediated Neovascularity Targeted Antitumor Drug Delivery System - Chengqun Chen; Huijuan Zhang; Lin Hou; Jinjin Shi; Lei Wang; Chaofeng Zhang; Mingyue Zhang; Hongling Zhang; Xiufang Shi; Huixiang Li; Zhenzhong Zhang (Frontiers Media S.A., 2013)
Purpose. The aim of this study was to prepare a new neovascularity targeting antitumor drug delivery system mediated by single-walled carbon nanotubes (SWNTs). Methods. In this study, antiangiogenesis agent 2-methoxyestradiol was loaded by SWNTs via π~π accumulation. The SWNTs were then linked with NGR (Asn-Gly-Arg) peptide, which could target tumor angiogenesis. This drug delivery system was characterized by transmission electron microscope, scanning electron microscopy, and atomic force microscope analysis. The suppression efficacy of tumor growth in cultured breast cancer cell line was evaluated by the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide assay. The in vivo antitumor activity was evaluated on the Sarcoma (S180) tumor-bearing mice model. Results. The characteristics of this drug delivery system showed that the particle of complex was 190 ± 4.3 nm in size distribution and 23.56 ± 2.03 mV in zeta potential. The inhibition ratio of this SWNTs drug delivery system at 24, 48, and 72 h was about 57.7%, 83.6%, and 88.2%. Compared with normal saline group, the relative tumor volumes in the 2ME, SWNTs-2ME, and NGR-SWNTs-2ME groups were decreased 1 week after administration. Conclusion. This novel neovascularity targeting drug delivery system containing NGR-SWNTs-2ME may be beneficial to improve treatment efficacy and minimize side effects in future cancer therapy. This article is open to POST-PUBLICATION REVIEW. Registered readers (see "For Readers") may comment by clicking on ABSTRACT on the issue's contents page.